Policy options for market-oriented livestock production by smallholder producers: The Casren Project - Lapar, Ma. Lucila (2003)
The population growth, urbanization, and income growth that fuelled the increase in meat and milk consumption during the last two decades are expected to continue in the future, creating a veritable "Livestock Revolution". This revolution presents new and expanding market opportunities for smallholder livestock producers. Inappropriate policies and misallocation of investment resources could, however, skew the distribution of the benefits and opportunities away from those smallholders who would potentially gain the most from this revolution. In this context, a search for policies designed to enhance the benefits to smallholders seems appropriate. This study provides an empirical basis for identifying options to increase the participation of smallholders in livestock markets in the Philippines. We present a model of household entry into markets where smallholders make decisions about participation (whether to sell quantities of products) and supply (how much of the various quantities to sell). The theory is implemented using probit and Tobit techniques that exploit Gibbs-sampling and data-augmentation. Application to a sample of Philippine smallholders reveals important insights about the competing influences of transactions costs, labour mobility, capital formation and credit use on the market participation and supply decisions. The offsetting impacts of conflicting factors complicate the roles for policy in the context of expanding the density of participation in the study site.